Analysis of Students Ecological Intelligence through Differentiated Learning in Social Studies Subjects at Elementary School - Ramdhani, Annita Suci; Supriatna, Nana (International Conference on Elementary Education, 2025)
This research aims to analyze students' ecological intelligence through differentiated learning in Social Studies (IPS) subjects in elementary schools. This research uses the Classroom Action Research (PTK) method which is carried out in class V of elementary school. The research subjects consisted of 36 students, with a focus on implementing diverse learning strategies to accommodate various student learning styles. Data was collected through observation, interviews and ecological intelligence tests. The research results show that the application of differentiated learning can significantly increase students' ecological intelligence. These findings indicate that diverse learning approaches can create learning environments that are more inclusive and responsive to student  needs, thereby fostering a better understanding of ecological issues. The results of the research that has been carried out are getting improvement from cycle 1 to cycle 2. It can be said that the implementation of the differentiation learning approach through the PBL model can be said to be successful. It is hoped that this research can become a reference for educators in developing more effective learning methods in the future.